Meta-analisis: Pengaruh Media E-learning Terhadap Keterampilan Berpikir Kritis dan Kreatif - Risda Putri Indriani; Diana Vivanti Sigit; Mieke Miarsyah (Jayapangus Press, 2023)
E-learning media is the result of technological developments that are currently used to support online and blended learning. Many researches on the development of e-learning media have been carried out, so a re-analysis is needed to find out how much influence the use of e-learning media has on critical and creative thinking skills. This study uses a meta-analysis technique by determining the effect size value. The sample used is 10 articles from 2011-2021. Based on the results of the analysis, it can be seen that the use of e-learning media has a major effect on critical and creative thinking skills. The e-learning media that has an effect on critical thinking skills is role play games (RPG). The e-learning media that has an effect on creative thinking skills is mobile learning. The effect of e-learning media on critical and creative thinking skills is highest at the high school education level. The biggest influence of the use of e-learning media on critical thinking skills is in Java Island, and on creative thinking skills is in the Maluku Islands.